2021
DOI: 10.1021/acs.chemrev.0c00830
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Energy Transduction by Charge Translocating Membrane Proteins

Abstract: Life relies on the constant exchange of different forms of energy, i.e., on energy transduction. Therefore, organisms have evolved in a way to be able to harvest the energy made available by external sources (such as light or chemical compounds) and convert these into biological useable energy forms, such as the transmembrane difference of electrochemical potential (Δμ). Membrane proteins contribute to the establishment of Δμb y coupling exergonic catalytic reactions to the translocation of charges (electrons/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 402 publications
0
46
0
Order By: Relevance
“…Our identification is supported by substitution studies of amino acid residues located at TMH 1-4 on our proposed N-side half-channel (Tyr106 PsrC_W and Glu146 PsrC_W ) and located at TMH 5-8 on the P-side half-channel (Glu225 PsrC_W , Ser185 PsrC_W , Ser188 PsrC_W and Tyr310 PsrC_W ) of W. succinogenes PsrC model, resulted in strains with a compromised polysulfide respiration (Dietrich and Klimmek, 2002). These data suggest those residues may be important for proton translocation, since PsrABC catalyzes an endergonic reaction dependent of electrochemical potential (Dietrich and Klimmek, 2002;Calisto et al, 2021).…”
Section: Ion Translocation Pathwaysmentioning
confidence: 69%
See 4 more Smart Citations
“…Our identification is supported by substitution studies of amino acid residues located at TMH 1-4 on our proposed N-side half-channel (Tyr106 PsrC_W and Glu146 PsrC_W ) and located at TMH 5-8 on the P-side half-channel (Glu225 PsrC_W , Ser185 PsrC_W , Ser188 PsrC_W and Tyr310 PsrC_W ) of W. succinogenes PsrC model, resulted in strains with a compromised polysulfide respiration (Dietrich and Klimmek, 2002). These data suggest those residues may be important for proton translocation, since PsrABC catalyzes an endergonic reaction dependent of electrochemical potential (Dietrich and Klimmek, 2002;Calisto et al, 2021).…”
Section: Ion Translocation Pathwaysmentioning
confidence: 69%
“…NrfD-like subunit-containing complexes were hypothesized to be capable of ion-translocation across the membrane (Calisto et al, 2021) and, in fact, proton-conducting pathways have been identified in the structures of the PsrC, ActC and ActF subunits (Jormakka et al, 2008;Sousa et al, 2018;Sun et al, 2018;Shi et al, 2020). Proton-conducting pathways are formed by amino acid residues with side chains that can establish hydrogen bonds, constituting a hydrogen bond network.…”
Section: Ion Translocation Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations